دراسة استبيانية حول استعمالات ثلاثة نبتات طبية صحراوية مستخدمة في طب التقليدي في ولاية الوادي - غزيل محمد الصغير (Université of Eloued, 2024)
In order to aid in the identification of medicinal plants in the Oued Souf region, we have chosen three plants: Atriplex halimus (L.), Matricaria Pubescens (Desf.) Schultz, and Citrullus colocynthis (L.). A questionnaire was distributed to a group of residents of the region consisting of herbal sellers, researchers, doctors in alternative medicine, and herbal users, numbering 40 questionnaires. from the group of residents in the area. The questionnaire included multiple choice questions about medicinal uses, studied plants, target organs, involved parties, and treatment methods. The results showed that M. Pubescens is primarily used to treat disorders of the digestive system and the respiratory system, while A. halimus is primarily used to treat disorders of the skin and respiratory system. C. colocynthis is primarily used to treat skin diseases and respiratory disorders. and illnesses related to the female reproductive system.
Keywords: Medical Plants; EL OUED; Questionnaire.